A Microporous MOF with Inorganic Nitrate Ions Immobilized on a Porous Surface Displaying Efficient C2H2 Separation and Purification. Issue 17 (7th April 2020) - Gao, Xiaoxia; Zhong, Haoyan; Zhang, Yingying; Yao, Yongna; Chen, De‐li; He, Yabing
Abstract : A microporous MOF based on a heterotopic ligand was successfully synthesized under solvothermal conditions and fully characterized using single‐crystal and powder X‐ray diffraction, TGA, FTIR, and microanalyses. Single‐crystal X‐ray diffraction analyses showed that the title MOF contains rich inorganic nitrate ions decorating the channel surface that can serve as C2 H2 recognition sites. Its selective gas adsorption properties towards C2 H2 over CO2 and CH4 were evaluated by single‐component equilibrium adsorption measurements and IAST calculations, establishing its promising potential for C2 H2 separation and purification. At ambient conditions, the C2 H2 uptake capacity reaches 92.2 cm 3 (STP) g –1, while the IAST‐predicted adsorption selectivities are up to 30.6 and 4.5 for the equimolar C2 H2 ‐CH4 and C2 H2 ‐CO2 binary gas mixtures, respectively. Furthermore, DFT computation studies revealed that the inorganic nitrate ion plays a very important role for preferential adsorption of C2 H2 over CO2 and CH4 . Abstract : A microporous MOF featuring inorganic nitrate ions immobilized on a porous surface was constructed Its function as C2 H2 recognition site exhibits promising potential for the separation of CO2 and CH4 from C2 H2 at ambient conditions.